(untitled) (Journal of Libya for geographical studies, 2022)
This study deals with the uses of land in Al-Badia city, where different patterns exist (residential, industrial, commercial, community service and agricultural) which differ in size and importance according to the domination of these different patterns and the reasons of their development. The constructional region was distinguished with dynamism and vitality and also rivalry for possession on lands. While some lands expanded and developed, others decreased to ample the scope for other uses. The city experienced a lot of problems that dealt with the uses of the land, as a result of accelerated urbanite growth arising from the confrontation of the migration waves, especially after the events of February 2011, and also, due to the change of govern system; furthermore, the natural increase of populations. Some factors such as political, economic, and social factors contributed directly to aggravating the problem of changes of land uses, especially the residential lands compared to the uses of lands to others such as agricultural lands, and covering natural plants, also the green areas, ;consequently, the city lost a big part of its urbanite characteristics, acquiring in return, in most of its suburbs and districts of buildings, a quality of randomness which seemed clear in their features. This study aims to shed light on the uses of land in Al-Badia city, which depended on geographic information system (GIS) and also on the technique of remote sensing (RS) as a practical basic technique in drawing out the area of those uses in the city and its patterns, as well as its distribution.